2018
DOI: 10.5858/arpa.2017-0471-oa
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Verified Assay for KRAS Mutation Detection in Tissue and Plasma of Lung, Colorectal, and Pancreatic Cancer

Abstract: - The KRAS Mutation Test v2 is a highly robust, reproducible, and sensitive test for the qualitative detection of 28 mutations in exons 2, 3, and 4 of the KRAS gene in both solid (tissue) and liquid (plasma) biopsies from colorectal cancer, non-small cell lung cancer, and pancreatic cancer, and is a convenient option for KRAS mutation testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the test involves many washing and incubation steps with a total analysis time of about 2 h [ 48 ]. Compared to the previously reported biosensors for ctDNA detection in real samples ( Table S3 ) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ], the advantages of the proposed multi-plex test are related mostly to the cost, run time, and simplicity, as well as the universality and advanced multiplexing potential.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the test involves many washing and incubation steps with a total analysis time of about 2 h [ 48 ]. Compared to the previously reported biosensors for ctDNA detection in real samples ( Table S3 ) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ], the advantages of the proposed multi-plex test are related mostly to the cost, run time, and simplicity, as well as the universality and advanced multiplexing potential.…”
Section: Discussionmentioning
confidence: 95%
“…In one recent study, authors found that only 42.8% of patients with EOPC expressed a KRAS mutation [10]. The common types of KRAS are on exon 2 codons 12 and 13 with relative frequency of 71-80% [35,36] and mostly located at G12C, G12D and G12R in pancreatic cancer [37,38]. There is no data on frequency in EOPC verses LOPC.…”
Section: Kirsten Rat Sarcoma Virus (Kras) Mutationmentioning
confidence: 99%
“…Mutations located in codons 12 and 13 are multiallelic, but the changes c.35G>A and c.38G>A (p.Gly12Asp and p.Gly13Asp, respectively) are the most common [11]. Additionally, the frequency of these mutations varies between populations in CRC patients, with an overall frequency of 33%-50% [12][13][14]. Besides the molecular variability in the KRAS gene, CRC also has a versatile clinical presentation.…”
Section: Introductionmentioning
confidence: 99%